Socialist Youth's International press-service. Ed. by the Office of the Socialists Youth International
Continued by: International socialist youth correspondence (ZK 16110). - For suppl. see: Communications of the Socialist Educational International (ZK 16110). - German ed.: Internationale sozialistische Jugendkorrespondenz (ZK 16109). - French ed.: Bulletin international de la Jeunesse socialiste (ZK 16112). - Scand. ed.: Internationale socialistiske ungdomsmeddelelser (ZK 16113).